Community Treatment Orders and Other Forms of Mandatory Outpatient Treatment. (May 2019) - O'Reilly, Richard L.; Hastings, Thomas; Chaimowitz, Gary A.; Neilson, Grainne E.; Brooks, Simon A.; Freeland, Alison
This position paper has been substantially revised by the Canadian Psychiatric Association's Professional Standards and Practice Committee and approved for republication by the CPA's Board of Directors on July 26, 2018. The original position paper 1 was first approved by the Board of Directors on January 25, 2003. It was subsequently reviewed and approved for republication with minor revisions on June 2, 2009.